Pengembangan Kurikulum Moderasi Islam (Wasathiyyah) dan Karakter Muslim Moderat yang Bertakwa di dalam Lingkungan Muhammadiyah - Abbas, Afifi Fauzi; Afifi, Abdullah A (IDRIS Darulfunun Institute, 2021)
The development of the Islamic moderation (wasathiyyah) concept is the backbone of forming a progressive Islam in Indonesia. Improving education within the Muhammadiyah is one of the significant contributions to developing Indonesian construct and education in Indonesia. The educational curriculum developed by Muhammadiyah responds to the sociocultural changes and challenges faced by education at Muhammadiyah and Indonesia in general. The developed curricula will continuously evaluate and improve to provide moderate (wasathiyyah ) and progressive (islah wa maslahah) human outcomes. In the end, the effort of developing education is to expect students to have a balanced faith and science; finally, it can be a solution for humankind. This paper reviews the author's experience in developing education in Muhammadiyah.